2010
DOI: 10.1002/elps.201000352
|View full text |Cite
|
Sign up to set email alerts
|

Sensitized phosphorescence as detection method for the enantioseparation of bupropion by capillary electrophoresis

Abstract: A new CE detection method was developed for the chiral drug bupropion (a second-generation antidepressant), based on phosphorescence both in the direct and in the sensitized mode using pulsed laser excitation at 266 nm. Electrokinetic chromatography using 5 mM sulfated-α-CD as chiral selector in 25 mM phosphate buffer at pH 3 allowed the separation of bupropion enantiomers with a high chiral resolution (Rs>3). In the sensitized phosphorescence detection mode, excitation energy is transferred from the analyte t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…A comparison in terms of sensitivity between direct phosphorescence and sensitized phosphorescence modes, which were employed as detection systems for the determination of bupropion enantiomers, is depicted in Fig. 6 60. As it can be observed in this figure, an improvement in the sensitivity of 40‐times was achieved using the sensitized phosphorescence mode.…”
Section: Approaches For Improving the Detection Sensitivitymentioning
confidence: 91%
See 1 more Smart Citation
“…A comparison in terms of sensitivity between direct phosphorescence and sensitized phosphorescence modes, which were employed as detection systems for the determination of bupropion enantiomers, is depicted in Fig. 6 60. As it can be observed in this figure, an improvement in the sensitivity of 40‐times was achieved using the sensitized phosphorescence mode.…”
Section: Approaches For Improving the Detection Sensitivitymentioning
confidence: 91%
“…Several works published by Gooijer's research group have demonstrated the potential of phosphorescence as detection technique in sensitive chiral analysis. In this works, LED 58 or Nd‐YAG laser 59, 60 was employed as excitation sources using a sensitized phosphorescence mode. As shown in Table 3, different EKC methods coupled to phosphorescence detection were developed for the determination of camphorquinone 58, 59 and bupropion 60 in standards and different real samples.…”
Section: Approaches For Improving the Detection Sensitivitymentioning
confidence: 99%
“…Next to fluorescence detection, which is well established in CE, room temperature phosphorescence (RTP) in liquid deoxygenated solutions was shown to be an attractive luminescence spectroscopic method for detection in CE [1927]. Apart from direct phosphorescence, where the analyte is excited by light of an appropriate wavelength and phosphoresces itself, several indirect phosphorescence modes can be distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…In one sensitized mode, the analyte is excited and transfers its excitation energy to a more strongly phosphorescent acceptor added to the background electrolyte (BGE), after which the emission of the latter is observed. That approach was used in a previous paper on the enantioseparation and phosphorescence detection of bupropion [27]. Alternatively, one can excite a donor reagent with excellent absorption properties, which then transfers its electronic energy to the analyte of which the emission is detected [28].…”
Section: Introductionmentioning
confidence: 99%
“…graphy (LC) [13][14][15], liquid chromatography mass spectrometry (LC-MS) [16], liquid chromatography--tandem mass spectrometry (LC-MS/MS) [17][18][19], liquid chromatography electrospray ionization-tandem mass spectrometry (LC/ESI/MS/MS) [20], capillary electrophoresis [21] and radioimmunoassay [22]. Several methods have been reported for the determination of BUPH in pharmaceuticals such as non--aqueous titration [23], HPLC [23][24][25][26], gas liquid chromatography (GLC) [27], LC [28], thin-layer chromatography (TLC) [29], capillary electrophoresis [21], polarography [30], potentiometry [31], conductometry [31], UV-spectrophotometry [31,32] and visible spectrophotometry [33,34].…”
mentioning
confidence: 99%